Implementasi Sistem Pengaturan Suhu Ruang Server Menggunakan Sensor DHT11 dan Sensor PIR Berbasis Mikrokontroler - Gunawan, Gunawan; Fatimah, Titin (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Temperature setting system is a very important system in the server room. Server room that has a high temperature, and humidity will be influencing the performance of the network device that causes a network device broke easily. And then, if the light in server room is continuously lit, it will cause the increase of room's temperature and waste electricity that impact on intensify electricity bill. Therefore, it needs a system that can protect devices, which saved in the server room, also can manage the server room. For resolving those problems, developed a tool that aims to control the temperature and the light in server room automatically monitoring the temperature and humidity. This system development method uses a prototype method that starts with interviewing IT staff directly, make and repair the prototype and IT staff, test and trying the prototype. Testing was done by using black box method testing. The test result obtained that DHT11 sensor can detect the temperature and humidity, IR Transmitter can control the Air Conditioner (AC), Passive InfraRed sensor can detect the movement and NodeMCU microcontroller can manage the tool, also send and save the temperature data and humidity in the database. The conclusion is system can control the temperature and monitoring the server room well and can control the light automatically.